2022
DOI: 10.1021/acs.orglett.2c02466
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Synthesis of Fused-Ring Tetrahydroisoquinolines and Tetrahydro-β-carbolines from 2-Arylethylamines via a Chemoenzymatic Approach

Abstract: While chiral fused-ring tetrahydroisoquinoline (THIQ) and tetrahydro-β-carboline (THβC) scaffolds have attracted considerable interest due to their wide spectrum of biological activities, the synthesis of optically pure chiral fused-ring THIQs and THβCs remains a challenging task. Herein, a group of active imine reductases were identified to convert the imine precursors into the corresponding enantiocomplementary fused-ring THIQs and THβCs with high enantioselectivity and conversion, establishing an efficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 61 publications
0
8
0
Order By: Relevance
“…A number of fused-ring THIQ and THβCs were synthesized at preparative scales including natural alkaloids with stereo-complementary IREDs in high yields (up to 85%) (Table 3, entry 35). 141…”
Section: Imine Reductases and Reductive Aminases (Ireds And Redams)mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of fused-ring THIQ and THβCs were synthesized at preparative scales including natural alkaloids with stereo-complementary IREDs in high yields (up to 85%) (Table 3, entry 35). 141…”
Section: Imine Reductases and Reductive Aminases (Ireds And Redams)mentioning
confidence: 99%
“…A number of fused-ring THIQ and THbCs were synthesized at preparative scales including natural alkaloids with stereo-complementary IREDs in high yields (up to 85%) (Table 3, entry 35). 141 Very recently, the Zheng group discovered an IRED from Penicillium camemberti (PcIRED). Targeting the calcimimetic drug Cinacalcet, ISM was performed on this enzyme.…”
Section: Discovery History Of Evolution and Substrate Scope Of Iredsmentioning
confidence: 99%
“…12 Very recently, the Qu group reported the efficient synthesis of 1aryl-THβCs using engineered IRED enzymes, 13 while the Zhu group disclosed the IRED-catalyzed asymmetric synthesis of fused-ring THβCs. 14 To the best of our knowledge, IREDcatalyzed reduction of DHβCs bearing a quaternary carbon attached to C1 has not been reported until now. Herein, we report the discovery, engineering, and application of IREDs for the asymmetric synthesis of chiral, sterically hindered 1substituted THβCs, including those containing a quaternary carbon (Scheme 1).…”
mentioning
confidence: 99%
“…There were reports on the IRED-catalyzed reduction of 1-substituted DHβCs to THβCs when we initiated our study . Very recently, the Qu group reported the efficient synthesis of 1-aryl-THβCs using engineered IRED enzymes, while the Zhu group disclosed the IRED-catalyzed asymmetric synthesis of fused-ring THβCs . To the best of our knowledge, IRED-catalyzed reduction of DHβCs bearing a quaternary carbon attached to C1 has not been reported until now.…”
mentioning
confidence: 99%
“…GF3546, respectively, possessing activity toward the substrate 2-methyl-1-pyrroline . In the past decade, research on IREDs has showed a booming development trend. Turner et al reported the discovery of a reductive aminase from Aspergillus oryzae ( Asp RedAm) that can catalyze the reductive coupling of a broad set of carbonyl compounds with a variety of primary and secondary amines . Gröger et al presented a panel of IREDs enabling the reduction of 3-thiazolines with high conversion and high to excellent enantioselectivity (>96% and up to 99% ee, respectively) .…”
mentioning
confidence: 99%